The crown of embers / 2. - Carson, Rae (Girl of fire and thorns ;, 2012)
Seventeen-year-old princess turned war queen Elisa, struggling to earn trust and respect inside her court, sets out on an adventure to find the mythical source of the Godstone's power as her country crumbles and her enemies resurface.